A Lutheran plague: murdering to die in the eighteenth century - Krogh, Tyge (Studies in Central European histories, 2012)
To kill someone purely in order to be sentenced to death and then to die at the hands of the executioner! Such murders were alarmingly frequent in eighteenth-century Lutheran Europe. The book traces the complex motives behind these crimes -- an investigation that leads not only to the Pietist interest in saving the souls of those sentenced to death but also into some of the central elements of Lutheran soteriology and the idea of capital punishment as being divinely ordained. The murders prompted special legislation and challenged the religious basis of the death penalty, and the killings and the logic behind them played an important role in debates about capital punishment, following Beccaria. Although much less frequent than in Lutheran Europe, such crimes are still committed elsewhere in eighteenth-century Europe, and even in the present-day US. Thus they seem to go hand in hand with the death penalty, irrespective of time and space